CEO Power, Corporate Governance Mechanisms and Earnings Quality - Dalia Ali Mostafa Hemdan; Saif-Ur-Rehman; Faisal Khan (Asian Academy of Management Journal of Accounting and Finance, 2023)
This article investigated the determinants of the firm’s earnings quality (FREQ) using panel data of Egyptian listed firms to address the concerns of endogeneity and heterogeneity. We found that CEO power dynamics negatively impact FREQ. Furthermore, corporate governance’s weakening or substitution role is investigated for the negative association between CEO power dynamics and FREQ. Our findings showed that board-independence significantly weakens the impacts of CEO- ownership and CEO-tenure on FREQ. In contrast, the results fail to support the weakening or substitution role of board-independence for the negative effects of CEO-duality and CEO-political connection on FREQ. Board gender diversity is not significantly associated with FREQ. However, we found that the presence of gender critical mass serves as a substitution mechanism for the negative association between CEO power dynamics and FREQ. Lastly, we observed strong robustness for our primary analysis through propensity matching scores and difference-in-different (DID) techniques. This study brings a novelty to existing research by exploring the negative consequences of CEO power dynamics. Furthermore, it provides an insight into the constraining or weakening of the role of corporate governance. The main findings of the current study are also robust to Modified Jones model (1995) reverse-causality, DID and propensity-matching techniques.